Implementasi Service Quality (Servqual) Terhadap Kepuasan Nasabah Pada PT. Bank Sinarmas Tbk - Ranti Anjelia; Asfia Fitri Aras; Corry Handayani (Jurnal INOVATOR, 2021)
Service quality is a very important factor and root that is capable of satisfying its customers. The purpose of this research is to determine the factors that determine service quality (servqual) on customer satisfaction at PT. Bank Sinarmas Tbk Kcp. Jambi Tebing Tinggi and knowing service quality (servqual) on customer satisfaction at PT. Bank Sinarmas Tbk Kcp. Jambi Tebing Tinggi. This study uses primary data that comes from direct observation and direct distributed questionnaires which are then analyzed using the servqual test and multiple linear regression tests. The results showed that customer satisfaction is influenced by the parking area, physical equipment owned, employee appearance, security facilities, fast service to customers, employee knowledge of bank products, personal attention to customers in terms of service and employee sensitivity to know customer interests (reality) and to determine service quality (servqual) to customer satisfaction, namely reliability, responsiveness, assurance and empathy, while the assessment of unsatisfied customers is tangible